Last call - Powers, Tim, 1952- (William Morrow, 2013)
Set in the gritty, dazzling underworld known as Las Vegas, Last Call tells the story of a one-eyed professional gambler who discovers that he was not the big winner in a long-ago poker game . . . and now must play for the highest stakes ever as he searches for a way to win back his soul.